Estimation of Parameters in Regression Analysis Based on QR Decomposition of Rectangular Matrices by Householder Reflections - Dorokhov, Oleksandr; Malyarets, Lyudmyla; Yevstrat, Dmytro; Ukrainski, Kadri (Informatica, 2022)
An approach to eliminate multicollinearity problems in regression analysis using QR decomposition of rectangular matrices by Householder reflection has been proposed. The reliability of this computational procedure has been proved. Povzetek: Predložen je pristup uklanjanju problema multikolinearnosti u regresijskoj analizi korištenjem QR dekompozicije pravokutnih matrica Householderovom refleksijom. Dokazana je pouzdanost ovog proračunskog postupka.